The frequency and pattern of thyroid disorders in pregnant women during the first antenatal visit (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Background: Maternal thyroid problems have been attributed to a spectrum of adverse pregnancy outcomes. Considering iodine deficiency in our population, screening for thyroid disorders during the first prenatal visit is important because early detection reduces the risk of complications for both mother and child by proper management.Objective: To determine the frequency and pattern of dysfunction in pregnant women who appeared to be in good health during their first antenatal visit, regardless of gestational age.Methods: A cross-sectional analysis was used in this study. A total of 1102 apparently healthy pregnant women were recruited during their first antenatal visit. Women with known thyroid disorders, chronic diseases, e.g., chronic kidney disease (CKD), chronic liver disease (CLD), or a history of taking drugs that interfere with thyroid function were excluded. TSH and FT4 levels were measured and evaluated according to reference intervals for thyroid hormones based on gestational age recommended by the American Thyroid Association (ATA) and according to conventional criteria. The Department of Microbiology and Immunology of Bangabandhu Sheikh Mujib Medical University (BSMMU) investigated lab variables.Results: The mean age of the participants was 25.7±5.0 years. The most frequent thyroid dysfunction was subclinical hypothyroidism, which was 50.5% in the second trimester, 28.8% in the first trimester, and 18.7% in the third trimester. According to ATA and conventional criteria, dysfunction was detected in 32.8% and 18.9% of participants, respectively. Goiter was present among 39.6% of participants. The odds for thyroid dysfunction in women with goiter were 2.5-fold in comparison to those without goiter (95% CI: 1.93-3.24; p